Strategi Literasi Dakwah Digital di Era Media Sosial TikTok: Tantangan dan Peluang - Ibad, M. Nashoihul (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
The development of digital technology has changed the communication landscape, including the spread of Islamic da'wah. As one of the fastest growing social media platforms in the world, TikTok has great potential to spread da'wah messages to a wider audience, especially the younger generation. However, the success of preaching on TikTok cannot be separated from the digital literacy of the preachers. Digital literacy is important to overcome several new challenges, including the spread of negative content, misinformation and disinformation that can damage the image of Islam. This research aims to identify effective digital literacy strategies for preachers who use TikTok as a medium for preaching. This study uses a qualitative approach to explore the challenges content creators face on TikTok, including how to manage content, build strong narratives, and interact with diverse audiences. In addition, this research examines the platform's ability to help TikTok reach a wider and more diverse audience, as well as the interactive features offered by TikTok in spreading da'wah, including interactive features used to enhance da'wah messages. We are also investigating opportunities to do this. The results show that a comprehensive digital literacy strategy, including understanding the TikTok algorithm, creativity in content creation, and audience interaction skills, will ensure the effectiveness of da'wah in improving this platform proves to be very important. With adequate content techniques, content creators can utilize TikTok's full potential to convey Islamic messages that are peaceful, inclusive and relevant to the challenges of the times.